Analysing trends in caesarean sections at a tertiary care teaching hospital in South India: findings from a clinical audit using Robson criteria - Yerra, Aruna Kumari; Khan, Mohammed Ismail (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section (CS) is a potentially life-saving surgery when performed for indicated reasons. The rates of CS deliveries have sky rocketed in the last few years. A CS does not come without complications and risk and therefore its trends in all institutes should be audited for ensuring optimization of obstetric care standards. Methods: The study was conducted as a retrospective analysis of all the CS deliveries for 12 months and their categorization using the WHO recommended Robson ten group classification system; with an aim to evaluate and understand the indication for each CS performed in the institute. The Robson was further subclassified to closely understand the circumstances in which the CS was performed in each group. Results: In this study evaluated a total of 2831 deliveries out of which 1557 (55%) were CS births. Out of these CS births, 48.5% were indicated for emergency indications. Class 5, 1 and 10 were the main contributors to the CS rate with 50.6%, 19.3% and 10% contributions respectively. From a total of 799 patients with previous CS, only 12.1% could have a successful trial of scar. The most common indications documented for Group 1 was foetal distress, cephalo pelvic disproportion and prolonged labour, in decreasing order. Among the singleton pre-terms who had a CS, a majority (92.3%) were operated before the onset of labour. Conclusions: The audit helped to understand the trends of CS in the institute and helped in the realizing that all the CS in the institute has questionable indications. This led to implementation of clinical and administrative reforms to ensure a reduction in unnecessary CS being performed.